Taxonomic studies on the genus Ophiopogon (Asparagaceae) I:—identity of O. albimarginatus and O. pseudotonkinensis, and a new species O. guangzhouensis from Guangdong, China - Gan, Xin-Jun; Feng, Hui-Zhe; Chen, Huan-Jin; Zhong, Ping-Sheng; Fan, Qiang (Phytotaxa, 2024)
One new species of Ophiopogon, O. guangzhouensis, from Guangdong Province in southern China, is described and illustrated. The new species is similar to O. bockianus, but differs markedly by its pedicel (1.3–1.7 cm long) longer than the stalky part of the floral base, adjacent anthers and filaments all completely connate, and style exerted beyond the tepals. This paper not only details their taxonomic features and relationships among similar species, but also provides data on the habitat and phenology of the new species. Based on critical observations on herbarium specimens (including type material) of nine other similar species, we also demonstrate that O. pseudotonkinensis is conspecific with O. bockianus and O. albimarginatus is synonymous with O. stenophyllus. We therefore reduce O. pseudotonkinensis and O. albimarginatus to the synonymy of O. bockianus and O. stenophyllus respectively.